Variation in rehabilitation setting after uncomplicated total knee or hip arthroplasty: a call for evidence-based guidelines - Justine M. Naylor; Andrew Hart; Ian A. Harris; Adriane M. Lewin (BMC Musculoskeletal Disorders, 2019)
Abstract Background High-level evidence consistently indicates that resource-intensive facility-based rehabilitation does not provide better recovery compared to home programs for uncomplicated knee or hip arthroplasty patients and, therefore, could be reserved for those most impaired. This study aimed to determine if rehabilitation setting aligns with evidence regardless of insurance status. Methods Sub-study within a national, prospective study involving 19 Australian high-volume public and private arthroplasty centres. Individuals undergoing primary arthroplasty for osteoarthritis participated. The main outcome was the proportion participating in each rehabilitation setting, obtained via chart review and participant telephone follow-up at 35 and 90 days post-surgery, categorised as ‘facility-based’ (inpatient rehabilitation and/or ≥ four outpatient-based sessions, including day-hospital) or ‘home-based’ (domiciliary, monitored or unmonitored home program only). We compared characteristics of the study cohort and rehabilitation setting by insurance status (public or private) using parametric and non-parametric tests, analysing the knee and hip cohorts separately. Results After excluding ineligible participants (bilateral surgeries, self-funded insurance, participation in a concurrent rehabilitation trial, experience of a major acute complication potentially affecting their rehabilitation pathway), 1334 eligible participants remained. Complete data were available for 1302 (97%) [Knee: n = 610, mean age 68.7 (8.5) yr., 51.1% female; Hip: n = 692, mean age 65.5 (10.4) yr., 48.9% female]; 26% (158/610) of knee and 61% (423/692) of hip participants participated predominantly in home-based programs. A greater proportion of public recipients were obese and had greater pre-operative joint impairment, but participated more commonly in home programs [(Knee: 32.9% (79/240) vs 21.4% (79/370) (P = 0.001); Hip: 71.0% (176/248) vs 55.6% (247/444) (P <  0.001)], less commonly in inpatient rehabilitation [Knee: 7.5% (18/240) vs 56.0% (207/370) P (< 0.001); Hip: 4.4% (11/248) vs 33.1% (147/444) (P <  0.001], and had fewer outpatient treatments [Knee: median (IQR) 6 (3) vs 8 (6) (P < 0.001); Hip: 6 (4) vs 8 (6) (P < 0.001)]. Conclusions Facility-based programs remain the norm for most knee and many hip arthroplasty recipients with insurance status being a major determinant of care. Development and implementation of evidence-based guidelines may help resolve the evidence-practice gap, addressing unwarranted practice variation across the insurance sectors.